Assessment of Visual Evoked Potential in the Non-diabetic Offspring of Type II Diabetic Individuals - A Cross Sectional Study - K Tamilselvan; Aruna Raju; Subhashri Soundirarajan; S Niveatha (TNOA Journal of Ophthalmic Science and Research)
Introduction: Visual evoked potential (VEP) is a non-invasive tool to detect retinopathy at early stages, and it can be used as a predictive marker for diabetic retinopathy. The study aimed to analyse VEP in non-diabetic offspring of type 2 diabetic and non-diabetic parents. Methodology: A cross-sectional observational study was conducted among 53 non-diabetic and normotensive offspring of type 2 diabetic and non-diabetic parents aged 18-25 years. Visual acuity and field of vision were assessed, and height, weight, and BMI were recorded. VEP was recorded using the standard operating procedure in the electrophysiology lab. Results: There is no significant difference in age, height, weight, and BMI between the two groups. Significant difference in P100 latency was observed in the right eye (P value is 0.003) and left eye (P value is 0.001) between offspring of diabetic parents and non-diabetic parents. Whereas no significant difference is observed in N75 latency, N 145 latency, and N75-P100 amplitude. Conclusions: The current study suggests that there is alteration in the VEP parameters in non-diabetic offspring of type 2 diabetic parents compared to offspring of non-diabetic parents.